SnRK1α1 Antagonizes Cell Death Induced by Transient Overexpression of Arabidopsis thaliana ABI5 Binding Protein 2 (AFP2) - Carianopol, Carina Steliana; Gazzarrini, Sonia (Frontiers in Plant Science, 2020)
Plants are continuously exposed to environmental stressors. They have thus evolved complex signaling pathways to govern responses to a variety of stimuli. The hormone abscisic acid (ABA) has been implicated in modulating both abiotic and biotic stress responses in plants. ABI5 Binding Proteins (AFPs) are a family of negative regulators of bZIP transcription factors of the AREB/ABF family, which promote ABA responses. AFP2 interacts with Snf1-Related protein Kinase 1 (SnRK1), which belongs to a highly conserved heterotrimeric kinase complex that is activated to re-establish energy homeostasis following stress. However, the role of this interaction is currently unknown. Here, we show that transient overexpression of Arabidopsis thaliana AFP2 in Nicotiana benthamiana leaves induces cell death. Using truncated AFP2 constructs, we demonstrate that CD induction by AFP2 is dependent on the EAR domain. Co-expression of the catalytic subunit SnRK1⍺1, but not SnRK1⍺2, rescues AFP2-induced CD. Overexpression of SnRK1⍺1 has little effect on AFP2 protein level and does not affect AFP2 subcellular localization. Our results show that a high level of AFP2 is detrimental for cell function and that SnRK1 antagonizes AFP2-induced CD most likely through a mechanism that does not involve AFP2 protein degradation or a change in subcellular localization.